Un = 5n - 2
The nth term is 2 + 3n.
I suspect that the first term should be "negative 3", ie the sequence is -3, 1, 5, 9, 13, 17, ... The nth term is 4n - 7
The nth term is 4n - 3
It is: 5n+3 and so the next term is 28
It is: 10n-7 and so the next term is 43
The nth term is: 5-2n
The differences are 3, 5, 7, 9,11, ... and the first term is -1; the nth term is: n² - 2
Nth term With the nth term you substitute the n for the term number (e.g. 50) so the 50th term in 2n+3 would be 2x50+3=103
The nth term of a sequence is the general formula for a sequence. The nth term of this particular sequence would be n+3. This is because each step in the sequence is plus 3 higher than the previous step.
2n + 1
20 - (3 * (n - 1))
The nth term in this sequence is 4n + 3.
The nth term is 18 -3n and so the next term will be 3
This appears to be a declining arithmetic series. If it is, the next term is 5, because each term is 3 less than the preceding term.=================================The 'N'th term is: [ 23 - 3N ].
The nth term is 2n+5 and so the next number is 17
If you mean: 15 11 7 3 then the nth term is 19-4n
It is 4n-13 and so the next number will be 11
The nth term would be -2n+14 nth terms: 1 2 3 4 Sequence:12 10 8 6 This sequence has a difference of -2 Therefore it would become -2n. Replace n with 1 and you would get -2. To get to the first term you have to add 14. Therefore the sequence becomes -2n+14. To check your answer replace n with 2, 3 or 4. You will still obtain the number in the sequence that corresponds to the nth term. :)
It is: nth term = 5-4n and so the next term will be -19
The nth term is 5n-3 and so the next term will be 22
This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term
13 and 14/42 = 13 and 1/3
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .